Greek Education in Great Britain - Louca-Crann, Margarita (Études helléniques / Hellenic Studies, 2005)
The author paints a historical fresco of the Cypriot and Greek community’s beginnings and development in the United Kingdom, especially in London. The article treats the various waves of immigration, basic community organizational structure, religious and educational influences on Greek-speaking immigrants and their children in Great Britain. The author concludes by recapitulating with details of the current situation of Greek-language learning in the UK and a strong recommendation to adopt the Paideia Omogenon material as soon and as broadly as possible.